Synthesis of NaAlH4/Al composites and their applications in hydrogen storage - Ianni, E.; Sofianos, M.; Rowles, Matthew; Sheppard, Drew; Humphries, Terry; Buckley, Craig (Elsevier Ltd, 2018)
© 2018 Hydrogen Energy Publications LLC In solid-state hydrogen storage in light metal hydrides, nanoconfinement and the use of catalysts represent promising solutions to overcoming limitations such as poor reversibility and slow kinetics. In this work, the morphology and hydrogen desorption kinetics of NaAlH4 melt-infiltrated into a previously developed Ti-based doped porous Al scaffold is analysed. Small-angle X-ray scattering and scanning electron microscopy analysis of low NaAlH4 loading in the porous Al scaffold has revealed that mesopores and small macropores are filled first, leaving the larger macropores/voids empty. Temperature-programmed desorption experiments have shown that NaAlH4-infiltrated porous Al scaffolds show a higher relative H2 release, with respect to NaAlH4 + TiCl3, in the temperature range 148–220 °C, with the temperature of H2 desorption trending to bulk NaAlH4 with increasing scaffold loading. The Ti-based catalytic effect is reproduced when the dopant is present in the scaffold. Further work is required to increase the mesoporous volume in order to enhance the nanoconfinement effect.